2022
DOI: 10.3390/bios12030175
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Sensors Based on Hydroxycarbazole for the Determination of Neurodegeneration-Related Halide Anions

Abstract: The environmental presence of anions of natural origin or anthropogenic origin is gradually increasing. As a tool to tackle this problem, carbazole derivatives are an attractive gateway to the development of luminescent chemosensors. Considering the different mechanisms proposed for anion recognition, the fluorescence properties and anion-binding response of several newly synthesised carbazole derivatives were studied. Potential anion sensors were designed so that they combined the native fluorescence of carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…It was shown that this sensor was able to recognize fluoride and chloride anions with high sensitivity by creating hydrogen bonding via hydrogen atoms in the pyrrolic nitrogen and hydroxy group. An increase in the fluorescence emission intensity of the sensor was observed with increasing amount of added anion [ 33 ]. Another group of anion sensors is halogen-bond-based chemosensors due to the possibility of halogen bond formation.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this sensor was able to recognize fluoride and chloride anions with high sensitivity by creating hydrogen bonding via hydrogen atoms in the pyrrolic nitrogen and hydroxy group. An increase in the fluorescence emission intensity of the sensor was observed with increasing amount of added anion [ 33 ]. Another group of anion sensors is halogen-bond-based chemosensors due to the possibility of halogen bond formation.…”
Section: Introductionmentioning
confidence: 99%